Evaluación y planteamiento de mejoras y redistribución de planta en un proceso de fabricación de bolígrafos mediante un modelo de simulación - Cabrera García, Marcela (2009)
This thesis is developed in a company that has been producing pens in the city of Guayaquil for the last 29 years, it belongs to a multinational founded in France in 1945, and since then has grown to the point to become the world leader in writing instruments. The company’s problems arise because the forecast indicates that the current demand will increase in an estimated of 10% per year on imported products, and 4.5% in sales of product manufactured in this plant, for this reason the company has been obliged to increase its available space for storage of imported products, increased the production capacity to supply the local market and satisfies the demand of its clients. In addition, the firm faces problems caused by the material handling system currently used, which affects the performance of the company's human resource and efficient travel of the pieces. The main obstacles the company has are: first, lack of storage capacity for the current and future finished product; second, the current handling material system has caused discomfort to the transportation, operator’s accidents and material losses; and third, the current distribution of the plant in which the interacting areas are remote from each other causing the parts to travel too much before the assembly. Once these problems has been identified, the solution approaches are established for each of them, this solutions are evaluated through the use of a simulation model, a tool to compare the results obtained by programming the current situation with those obtained with the proposals for improvement. These approaches are evaluated financially as the final part of the sequence analysis that has been done along this thesis.